On-Site Determination of Methylmercury by Coupling Solid-Phase Extraction and Voltammetry - Paolo Inaudi; Elio Mondino; Ornella Abollino; Mery Malandrino; Monica Argenziano; Laura Favilli; Roberto Boschini; Agnese Giacomino (Molecules, 2022)
A measurement and speciation procedure for the determination of total mercury (HgTOT), inorganic mercury (HgIN), and methylmercury (CH3Hg) was developed and the applicability for on-site determination was demonstrated. A simple, portable sample pretreatment procedure was optimized to extract the analytes. Home-made columns, packed with a new sorbent material called CYXAD (CYPHOS 101 modified Amberlite XAD), were used to separate the two forms of the analyte. HgTOT and CH3Hg were determined by anodic stripping voltammetry (ASV), using a solid gold electrode (SGE). Two certified reference materials (BCR-463 Tuna Fish and Tuna Fish ERM-CE 464) and eight fresh fishes were analyzed. Then, the results that were obtained following the optimized portable procedure were compared with the concentrations obtained, using a direct mercury analyzer (DMA). This quantification, using the two techniques, demonstrated the good performance of the proposed method.